Antecedents of the Digitization of Small and Medium Enterprises: Case in Sumedang Indonesia - Diana Sari; Kurnia Khafidhatur Rafiah; Wa Ode Zusnita Muizu; Amelia Rizky Alamanda (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
This study aims to analyse digital readiness of SMEs (Small and Medium Enterprises), especially in Sumedang district, as well as what factors must be optimized for SMEs to be able to adopt the development of digitalization. Quantitative and qualitative methods were used simultaneously in this research. Questionnaires were distributed offline and online through exhibitions, communities, community service activities, and social media. However, the data has been collected and valid is 182 data. As for calculating the level of digitization, it was adapted from the calculations carried out by previous researchThe results of data processing show that level of digital readiness of SMEs in Sumedang is still low, it’s at level 1 (Digital outsider). The results showed that from 5 variables: people, strategy, process, integration, and technology, the majority of SMEs in Sumedang were more prepared in terms of process and integration. The findings of this study indicate various parties who support development of SMEs towards digitalization must pay attention to readiness of SMEs and optimize assistance and/or training on aspects that hinder the adoption of digitalization such as lack of knowledge about service providers and technology, increase collaborating, etc.